Scope of Pharmacovigilance for Ayurvedic Drugs in Nepal: A Review - Pandit1, Ram Deo; Upadhyaya, Ashwani; Sharma, Navneet; Gupta, Chandni; Ritika (International Research Journal of Ayurveda & Yoga, 2024)
Ayurveda along with complementary and alternative medicine (CAM) systems have their own principles, have their own pharmacopeia, but are practiced as over the counter drugs without an authentic prescription. Government of Nepal nominated Department of Drug Administration (DDA) in October 2004 as the focal point (National Pharmacovigilance Centre) to liaison with WHO collaborating centre for International Drug Monitoring (IDM), Sweden and started collecting adverse drug reactions (Nepal became a WHO program member in July 2006). Nepal joined the international pharmacovigilance program as a full member in 2007. This study is to reflect the present status of pharmacovigilance in Nepal and put light on scope of pharmacovigilance on drugs of Ayurveda and other complementary alternative systems in Nepal. For which review and analysis of concerned published literatures in print form and in online database. At present; 12 regional pharmacovigilance centers are there in Nepal. Currently, the clear pattern and scope of adverse drug reactions (ADRs) in Nepal remains unexplored. For Ayurveda drugs the concept of pharmacovigilance is not yet formally introduced in Nepal. No policy has been formulated for the same. The conventional belief that Ayurveda drugs have no ADRs should be transformed.